OPTIMALISASI PENGETAHUAN DAN KETERAMPILAN KPM (KADER PEMBANGUNAN MANUSIA) MELALUI PENDAMPINGAN PEMANFAATAN PANGAN LOKAL SEBAGAI MENU DASHAT DI DESA DENAI KUALA - Berutu, Nurmala; Diningrat, Diky Setya; Hodriani; Rahmi, Anna; Junaidi (Universitas Mataram, 2024)
The issue of stunting in Indonesia remains high, with a percentage of 21.6%. As a result, Presidential Regulation No. 72 of 2021 was issued regarding the Acceleration of Stunting Reduction, with the target for Indonesia to reduce stunting to 14%. In North Sumatra, the stunting rate reaches 21.1%, with Denai Kuala Village having a rate of 22.4%. One of the efforts by the village government to accelerate the reduction of stunting is the formation of the DASHAT team (Dapur Atasi Stunting) and Kader KPM. Therefore, accurate and relevant knowledge about stunting is a key focus that must be emphasized in the role of KPM. The purpose of this research is to assess the extent of KPM's knowledge about stunting and how that knowledge has encouraged them to optimize their role in the acceleration of stunting reduction. The methodology includes preparation, implementation, and evaluation. In the evaluation, the research design is a pre-experimental design using a single group with pretest and posttest. The results show that the assistance provided has a positive effect on the knowledge and skills of Kader KPM in efforts to accelerate stunting reduction. There was an average increase in knowledge from 56.4 before the socialization and assistance to an average score of 84.1 after the socialization and assistance were conducted.